Civil engineering heritage. - Otter, R. A. (Thomas Telford, 1994)
This guide covers from Cornwall to Kent, including Somerset and parts of Wiltshire and Surrey. It provides an informative look at some of the internationally renowned examples of historic development and engineering skills throughout southern England including such examples as: Smeaton's Eddystone Lighthouse.